MONITORING OF SALMONELLOSIS RESISTANCE OF INDUSTRIAL CHICKEN FARMING IN ALMATY REGION OF KAZAKHSTAN (Experimental biology, 2024)
Salmonellosis is a common digestive infection of the food chain, so it is important to provide biological protection of poultry farms to exclude economic losses and prevent horizontal transfer of Salmonella bacteria through chicken products (eggs, meat) to humans. The aim of the study was to conduct comprehensive monitoring and study the resistance of industrial chicken farming in some poultry farms in Almaty region of Kazakhstan to bacteria of the genus Salmonella. The direction and idea of the research is that the strategy of salmonellosis control at poultry farms is based on two fundamental aspects: to reduce the level of spread of Salmonella bacteria among farm chickens at poultry farms and to protect the population of Kazakhstan from infection. Monitoring of resistance of industrial chicken farming to bacteria of the genus Salmonella for poultry farms is relevant and has scientific and practical value, as it contributes to the proper procedures for epidemiological surveillance and prevention, improvement of existing control measures, optimization of sampling methods and detection of bacteria of the genus Salmonella on poultry farms. The research methodology was based on weekly sampling from the environment of poultry farms in Almaty region of Kazakhstan and determination of the presence of bacteria of Salmonella genus in the selected samples by culture and biochemical methods. Samples from the technological facilities of poultry farms were taken from the entire calendar year. A total of 5672 samples were collected for testing, including 537 samples of litter, 3838 samples of flushes, 1024 samples of eggs, 181 samples of dust, 43 samples of straw, 49 samples of transport crates, litter paper and cardboard used for transport crates. Of the 5672 samples tested, the presence of Salmonella bacteria was recorded in 24 samples (0.5% of all samples tested). The results of these studies showed that detection of Salmonella bacteria in the tested samples is an effective method of biosecurity management for poultry farmers and allows them to quickly find sanitary and zoohygienic solutions in order to prevent the threat of Salmonella bacteria in chicken farms. Therefore, the efforts of poultry farms to reduce the transmission of Salmonella bacteria through chicken products should be realized on the scale of Kazakhstan.
Keywords: Salmonella, poultry production, farm chickens, monitoring, biosafety